2018
DOI: 10.3390/f9120779
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction of Growth and Stem Quality Traits in Eucalyptus globulus Labill. at Its Southernmost Distribution Limit in Chile

Abstract: The present study was undertaken to examine the ability of different genomic selection (GS) models to predict growth traits (diameter at breast height, tree height and wood volume), stem straightness and branching quality of Eucalyptus globulus Labill. trees using a genome-wide Single Nucleotide Polymorphism (SNP) chip (60 K), in one of the southernmost progeny trials of the species, close to its southern distribution limit in Chile. The GS methods examined were Ridge Regression-BLUP (RRBLUP), Bayes-A, Bayes-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…For instance, Callister et al [53] reported a range in branching quality (measured as branch thickness) of 0–0.16 in full-sib families of E. globulus (at age 3.5). Ballesta et al [43] reported that the pedigree-based heritability estimate of BQ in E. globulus at 4 years of age was less than 0.1. In other tree species, traits related to branch quality have been described to be moderately heritable [66,67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Callister et al [53] reported a range in branching quality (measured as branch thickness) of 0–0.16 in full-sib families of E. globulus (at age 3.5). Ballesta et al [43] reported that the pedigree-based heritability estimate of BQ in E. globulus at 4 years of age was less than 0.1. In other tree species, traits related to branch quality have been described to be moderately heritable [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are few studies that have evaluated the combined use of GS and haplotypes in plants [29,41,42]. In particular, these methods have been implemented in predominantly self-pollinated (autogamous) species—for example, soybean and wheat [41,42]—in which extensive LD values can be found in their genomes, which favors the identification of haplotypes, while in outcrossing species (allogamous) such as Eucalyptus and most species of forest interest, LD usually decays at short genomic distances [43,44], which allows the identification of smaller haplotype blocks and those conformed by a smaller number of alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the potential of the selection based on genomic tools in forest species [33][34][35][36], including E. cladocalyx [12,37,38]. According to the results, GSq models outperformed traditional GS models in terms of predictive ability when at least ten significant marker-trait associations were included in GSq.…”
Section: Comparison Between Genomic Prediction Modelsmentioning
confidence: 99%
“…According to Silva et al [19], the superior performance of the models that include QTL information compared with GS model can be due to GSq model exploiting relevant regions not directly considered in GS model, improving the performance of the prediction model. Additionally, previous studies have reported that a pre-selection of SNPs or the use of genome-wide association analyses to identify and rank markers could increase predictive ability [38,44,45].…”
Section: Comparison Between Genomic Prediction Modelsmentioning
confidence: 99%
“…E. globulus is the second most important woody species in the Chilean forest industry (Ballesta et al 2018), where it comprises approximately 21% of national plantations (Morales et al 2015). Traditionally, the species has experienced a rotation period that varies between eight and 12 years.…”
Section: Introductionmentioning
confidence: 99%